Gastrointestinal lipoma presenting as colonic intussuception: report of two cases. - Medhi, Pranita; Sharma, Mahak; Biswas, Manjusha (Annals of Pathology and Laboratory Medicine, 2015)
Lipomas are benign mesenchymal tumors of adipose tissue, though common at other sites, are rare in GIT. Most gastrointestinal lipomas are located in the colon, ileum and jejunum, are rarely responsible for clinical symptoms and are usually detected incidentally at colonoscopy. We present two such cases of large colonic lipomas. One is a 38-years old female presenting with complaint of loose stool and sessile mass in transverse colon on colonoscopy, suspected to be a malignant lesion. The other is a 40 years old female presenting with acute abdomen, colonoscopy revealed a submucosal mass in descending colon. Both underwent resection of mass, and histologically were revealed to be lipomas of colon. Colonic lipomas, although unusual, continue to present difficulties in the preoperative differentiation between malignant and benign colonic neoplasm. Two cases of colonic lipomas are reported.